Prolegomena for a Comparative Approach to Cypriot Literatures - Kappler, Matthias (Études helléniques / Hellenic Studies, 2007)
This article focuses on the concepts of literature and identity. The author advocates that “Cypriot literatures” are included into a broader contact area of the Middle East. Furthermore, he suggests the periphery/centre pattern which, according to him, perfectly applies to Cypriot literatures in a comparative approach.